A Study of Clinical Profile of Diabetic Ketoacidosis - Afshan, Javeria; K, Prabhakar; J, Sanketh; Anitha, Anitha; Afreen, Fareeha (Journal of Neonatal Surgery, 2025)
Background: Due to the increasing burden of diabetes mellitus, it is very important to assess the clinical profile of its complications, especially the lethal complication, diabetic ketoacidosis (DKA). Methods: This cross sectional study was conducted in the department of General Medicine at Sri Devaraj URS Medical College, during the period of June 2021 to September 2021. Study population includes 44 cases with diabetic ketoacidosis. Results: In this study, 90.9% of cases survived and it was noted that infection being the predisposing factor for the occurrence of DKA. Also the mean difference in total leucocytes counts was significantly elevated among the cases with bad outcome compared to survived cases. Conclusion: Infection, among the cases with diabetes mellitus should be addressed promptly because it predispose to DKA among the cases with uncontrolled diabetes mellitus.